In transit metastases in children, adolescents and young adults with localized rhabdomyosarcoma of the distal extremities: Analysis of the EpSSG RMS 2005 study. Issue 7 (July 2022) - Terwisscha van Scheltinga, C.E.J.; Wijnen, M.H.W.A.; Martelli, H.; Guerin, F.; Rogers, T.; Craigie, R.J.; Burrieza, G. Guillén; Dall'Igna, P.; De Corti, F.; Smeulders, N.; van Rijn, R.R.; Fajardo, R.Dávila; et al.
Abstract: In-transit metastases (ITM) are defined as metastatic lymph nodes or deposits occurring between the primary tumor and proximal draining lymph node basin. In extremity rhabdomyosarcoma (RMS), they have rarely been reported. This study evaluates the frequency, staging and survival of patients with ITM in distal extremity RMS. Methods: Patients with extremity RMS distal to the elbow or knee, enrolled in the EpSSG RMS 2005 trial between 2005 and 2016 were eligible for this study. Results: One hundred and nine distal extremity RMS patients, with a median age of 6.2 years (range 0–21 years) were included. Thirty seven of 109 (34%) had lymph node metastases at diagnosis, 19 of them (51%) had ITM, especially in lower extremity RMS. 18 F-FDG-PET/CT detected involved lymph nodes in 47% of patients. In patients not undergoing 18 F-FDG-PET/CT lymph node involvement was detected in 22%. The 5-yr EFS of patients with ITM vs proximal lymph nodes vs combined proximal and ITM was 88.9% vs 21.4% vs 20%, respectively (p = 0.01) and 5-yr OS was 100% vs 25.2% vs 15%, respectively (p = 0.003). Conclusion: Our study showed that in-transit metastases constituted more than 50% of all lymph node metastases in distal extremity RMS. 18 F-FDG-PET/CT improved nodal staging by detecting more regional and in-transit metastases. Popliteal and epitrochlear nodes should be considered as true (distal) regional nodes, instead of in-transit metastases. Biopsy of these nodes is recommended especially in distal extremity RMS of the lower limb. Patients with proximal (axillary or inguinal) lymph node involvement have a worse prognosis.